BAHAN AJAR KETERAMPILAN BERBAHASA INDONESIA BAGI PENUTUR ASING (BIPA) - Simarmata, Natalia Lia; Waruwu, Kasih Kristina; Khairani, Putri; Ratnawati, Fitria; Nasution, Jamaluddin (Vernacular: Linguistics, Literature, Communication and Culture Journal, 2024)
Indonesian as the national language has so far experienced very rapid development so that it is in great demand from other countries. This development has made Indonesian ready to become an international communication tool. In order to become an international language, it is necessary to introduce Indonesian with interesting learning. Interesting learning by designing innovative teaching materials. Teaching materials for listening, reading, writing and speaking language skills for level A1. In addition, BIPA teaching materials take advantage of existing cultures in Indonesia by introducing Indonesian characteristics to foreign speakers in the hope that this will attract them to learn Indonesian. This study uses a qualitative approach with a descriptive method. By describing teaching materials for Indonesian language skills, it will increase learning knowledge for BIPA teachers.